Direct-Acting Antiviral Therapy in Patients with Chronic Hepatitis C Shows Liver Fibrosis Regression on Three Noninvasive Tests: A Puerto Rican Cohort - López-Marte, Paola; Goyco-Cortés, Bianca; Rosado-Carrión, Bárbara (Puerto Rico Health Sciences Journal, 2024)
Objective: Direct-acting antiviral (DAA) drugs have resulted in high rates of virological cure in chronic hepatitis C (CHC)–infected patients. We used noninvasive tests to assess fibrosis in subjects who had been cured with DAA. Methods: Retrospective data collection (2014-2019) from the medical record of CHC patients at the hepatology clinic was performed. Subjects co-infected with HIV and hepatitis B, post–liver transplant, and lost to follow-up were excluded. We evaluated fibrosis at baseline and 1 year after completing therapy using vibration-controlled transient elastography (VCTE), fibrosis-4 (FIB-4), and aspartate aminotransferase-toplatelet ratio index (APRI) scores. Results: With 210 medical records reviewed, 41 were included. The mean age was 62.8 years; 61% were men. Significant fibrosis regression was observed 1-year post-treatment using 3 noninvasive methods: VCTE, APRI, and FIB-4 score. Prior to treatment, 46% of the patients had advanced fibrosis compared to 25% 1 year after treatment. The VCTE scores of 4 subjects (with body mass indices [BMIs] > 30) indicated a worsening of fibrosis. We did not find a statistically significant association between BMI and VCTE, FIB-4, or APRI score. Conclusion: In most CHC patients, DAA therapy leads to liver fibrosis regression. Obesity may play an important role in the worsening of hepatic fibrosis or the absence of fibrosis regression.